2006
DOI: 10.1149/1.2186184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Anode-Supported SOFCs Using a Thin Ce[sub 0.9]Gd[sub 0.1]O[sub 1.95] Electrolyte with an Incorporated BaCe[sub 0.8]Y[sub 0.2]O[sub 3−α] Layer in Hydrogen and Methane

Abstract: Multilayered Ce 0.9 Gd 0.1 O 1.95 /BaCe 0.8 Y 0.2 O 3−␣ /Ce 0.9 Gd 0.1 O 1.95 ͑GDC/BCY/GDC͒ electrolytes were prepared by tape casting on a Ni-Ce 0.8 Sm 0.2 O 1.9 anode support. The overall electrolyte thickness ranged from 30 to 35 m, including a 3 m thick BCY layer. When the multilayered electrolyte cell was tested with hydrogen at the anode and air at the cathode in the temperature range of 500-700°C, it yielded open-circuit voltages ͑OCVs͒ of 846-1024 mV, which were higher than the OCVs of 753-933 mV obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 29 publications
0
41
1
Order By: Relevance
“…On the other hand, our cell performances are lower than those reported under similar cell conditions (anode-supported, 10-20 lm electrolytes) by Shao et al and Zhang et al [8,22]. The use of cathode LSC instead of BSCF, LSCF or SSC can partially explain these differences in performance, because the LSC overpotential is higher than those of BSCF, LSCF or SSC [12,23]. However, there are other reasons that could justify the low performance of our cell.…”
Section: Original Research Papercontrasting
confidence: 74%
“…On the other hand, our cell performances are lower than those reported under similar cell conditions (anode-supported, 10-20 lm electrolytes) by Shao et al and Zhang et al [8,22]. The use of cathode LSC instead of BSCF, LSCF or SSC can partially explain these differences in performance, because the LSC overpotential is higher than those of BSCF, LSCF or SSC [12,23]. However, there are other reasons that could justify the low performance of our cell.…”
Section: Original Research Papercontrasting
confidence: 74%
“…Tomita et al [163] found that the addition of a thin BaCe 0.8 Y 0.2 O 3- (BCY) layer between two layers of GDC increased the stability of ceria-based electrolytes in reducing atmospheres. The laminated three-layer electrolyte impeded electronic short circuiting which occurs from electronic conductivity due to reduction of GDC at low oxygen partial pressure.…”
Section: Electrolyte Materialsmentioning
confidence: 99%
“…Doped ceria displays mixed conductivity (ionic and electronic) when it is placed in the reducing atmosphere, and this elecronic conduction causes leak current, leading to lower OCV. However, there are several reports to minimise the efficiency drop and they should be taken into account for the use of ceria-based electrolyte for application use [28,29]. Figure 4 shows the output current at the voltage of 2.1 V (0.7 V per bundle) for various fuel flow rates at 500°C operating temperature.…”
Section: Methodsmentioning
confidence: 99%